Additions to Meliolaceae from India - H. BIJU; G.R. ARCHANA, V.B. HOSAGOUDAR*, D.K. AGARWAL (Indian Phytopathology, 2006)
This paper deals with the descriptions of six meliolaceous fungi collected from the Southern Western Ghats of Karnataka State. Of these, Meliola cynanchi, M. pterigotae and M. strombosiae are the new species, while, M. desmodii-laxiflori var. indica, M. kanniyakumariana var. brahmagiriense and M. tabernaemontanae var. wrightiae are the new varieties described and illustrated in detail.